A comparative clinical study of arthrogenous versus myogenous temporomandibular disorder in patients presenting with Costen's syndrome. Issue 5 (3rd September 2021) - Effat, Kamal G.
ABSTRACT: Objective : Costen's syndrome involves otoneurological and sinonasal symptoms associated with temporomandibular disorder (TMD). The current study compared the symptoms related to Costen's syndrome in patients with arthrogenous versus myogenous TMD. Methods : The study involved 294 consecutive patients with TMD, prospectively examined over a period of 6 months. These were stratified into 180 patients with arthrogenous TMD and 114 patients with myogenous TMD. A questionnaire and examination protocol was applied for each patient. Results : Sinonasal symptoms were more common in the arthrogenous group ( p = .001), whereas, hearing loss and vertigo were more common in the myogenous group ( p = .001). Conclusion : The current study provides support for central nervous system neuroplastic changes in the genesis of Costen's syndrome symptoms.